2019
DOI: 10.1016/j.matt.2019.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Uniform, Scalable, High-Temperature Microwave Shock for Nanoparticle Synthesis through Defect Engineering

Abstract: We demonstrate an ultrahigh-temperature thermal shock method for nanoparticle synthesis using microwave irradiation. With proper defect engineering, microwave absorption of 70% was achieved, leading to the instant temperature increase to 1,600 K in 100 ms, followed by rapid quenching to room temperature. During such extreme temperature change, the precursors are decomposed and reconstructed into nanoparticles with small size and uniform distribution. This facile, rapid, and universal synthesis technique has po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 54 publications
0
53
0
1
Order By: Relevance
“…How to remove these organic groups without changing the shape and size is a difficult issue, because the common heating method would easily lead to the destruction of its ultrathin structure [45]. Recent studies have shown that, due to the generation of eddy currents, metallic graphene itself will be heated at a very fast rate (2000 K/0.1s) under microwave irradiation, thereby greatly improving its crystallinity and even decomposing the metal salts adsorbed on its surface [46,47]. Inspired by these work, since Ti 3 C 2 also has good electrical conductivity [48,49], can it also achieve an increase in crystallinity and elimination of organic groups through the extremely fast microwave heating?…”
Section: Introductionmentioning
confidence: 99%
“…How to remove these organic groups without changing the shape and size is a difficult issue, because the common heating method would easily lead to the destruction of its ultrathin structure [45]. Recent studies have shown that, due to the generation of eddy currents, metallic graphene itself will be heated at a very fast rate (2000 K/0.1s) under microwave irradiation, thereby greatly improving its crystallinity and even decomposing the metal salts adsorbed on its surface [46,47]. Inspired by these work, since Ti 3 C 2 also has good electrical conductivity [48,49], can it also achieve an increase in crystallinity and elimination of organic groups through the extremely fast microwave heating?…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] The desire to fabricate metallic nanoalloys with controllable size and composition is oen for an enhancement in specic properties due to their high specic surface area, rich diversity of compositions and structures, and their synergistic effects. [10][11][12][13][14][15][16][17] Previous studies have shown that Pt-based alloys present good catalytic activity as an ideal catalyst for the hydrogen evolution reaction, oxygen reduction reaction, and ethanol oxidation reaction. [18][19][20][21][22][23][24] At the same time, the alloying of low-cost transition metals and precious metals can effectively reduce the amount of precious metals and control costs.…”
Section: Introductionmentioning
confidence: 99%
“…25 However, current methods of manufacturing alloys are generally complicated and time consuming, and therefore it is very important to develop a convenient, efficient, and rapid method of manufacturing alloys. 12,26,27 Commonly, the wet chemistry synthesis of well-dispersed alloy NPs needs the assistance of organic surfactants or capping agents, such as cetyltrimethylammonium chloride, ethylene glycol, oleic acid, or oleylamines, to protect them from agglomeration. [28][29][30][31][32][33] Nevertheless, the residual surfactants are oen difficult to remove completely, which makes it difficult to obtain nanocrystals with clean surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31] For the last decade, solvent-free microwave irradiation synthesis methods have been gradually developed [32][33][34][35][36][37][38] and some novel uses of solvent-free microwave irradiation have been explored such as microwave carbonization 39 and the synthesis of nanoparticles. 36 Previous studies showed that graphene can effectively absorb microwaves and generate a lot of heat and the temperature can rapidly rise above 1000 C in a few seconds, and the particles loaded on the graphene can transform into nanoparticles from microparticles. 36 These facts inspire us to use this method to treat MoS 2 /graphene composites or similar congurations to remove the chemical modiers or cross-linkers and reduce graphene in a short time to improve the electrochemical performance of composite electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…36 Previous studies showed that graphene can effectively absorb microwaves and generate a lot of heat and the temperature can rapidly rise above 1000 C in a few seconds, and the particles loaded on the graphene can transform into nanoparticles from microparticles. 36 These facts inspire us to use this method to treat MoS 2 /graphene composites or similar congurations to remove the chemical modiers or cross-linkers and reduce graphene in a short time to improve the electrochemical performance of composite electrodes.…”
Section: Introductionmentioning
confidence: 99%